Performance Analysis and Dimensional Optimization of a 2R1T Parallel Mechanism with Remote Center of Motion - Huang Xin; Che Linxian; Li Jie; Du Li (Jixie chuandong)
Compared with serial mechanisms, parallel mechanisms have the advantages of good rigidity, high precision, stable and compact structure, which are suitable for the field of surgery. A (5R)OC-URR parallel mechanism with two rotational and one translational degrees of freedom and remote center of motion (RCM) is proposed which can be used for the body structure of minimally invasive surgery and has the characteristics of partial motion decoupling. The position analysis model of the mechanism is established, and the analytical expression of position of the inverse solutions is derived. On this basis, the desired workspace of the mechanism is defined for the task of minimally invasive surgery. Using the evaluation index of local motion/force transmissibility, the definition and calculation method of average transmission index in the desired workspace of the mechanism are given. Aiming at maximizing the average transmission index, a constrained optimization model of mechanism dimensional parameters is established, and the accelerating grey wolf optimization (AGWO) algorithm is employed to solve the problem. The test of numerical examples shows that the comprehensive performance of AGWO algorithm in solving constrained optimization problems is better than that of the compared algorithm. The results of mechanism optimization design show that the optimization model and algorithm are feasible and effective. The research work in this study can lay a theoretical foundation for the practical application of the mechanism.